Pelatihan Pembuatan Bahan Ajar Digital Berbasis Flipbooks bagi Guru di Kota Pekanbaru Riau - Yulis, Putri Ade Rahma; Dafit, Febrina; Fitriani, Fitriani; Amnestya, Prilla (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This community service activity aims to enhance the knowledge and skills of teachers in creating digital teaching materials based on flipbooks to realize a multimedia-based Islamic school. The implementation method of this community service involved training and mentoring 34 teachers at Arsyad Islamic School in Pekanbaru. The instruments used include questionnaires on the percentage of technology usage in teaching and questionnaires on the teachers' abilities related to using digital teaching material creation applications, which were then analyzed descriptively. The results of this community service showed that there was an improvement in teachers' understanding of the role of technology in teaching and their ability to produce digital learning resources such as flipbooks. Before the training, 48.4% did not master the skills, 31.3% had a sufficient level of mastery, 18.8% were proficient, and 0% were highly proficient in creating digital teaching materials. After the training, there was an improvement, with 0% having no mastery, 34.4% having a sufficient level of mastery, 50% being proficient, and 12.5% being highly proficient. It indicates that the community service activity has impacted teachers' understanding and skills.